Components of the frailty phenotype as predictors of mortality among older adults after four years of hospital discharge (Research, Society and Development, 2022)
Objective: to verify the association between impairment of frailty phenotype components as predictors of mortality among older adults after four years of hospital discharge. Methodology: Prospective and longitudinal investigation, carried out with hospitalized older adults, at baseline, and followed up after hospital discharge. Of the 163 older adults included in the study, 43 died during follow-up and 92 completed the four-year follow-up. The following instruments were used: Mini Mental State Examination, a form for characterizing sociodemographic, economic and health data; and Fried's frailty phenotype. Survival analysis was performed using the Kaplan-Meier method and Cox regression to estimate the risk ratio (Hazard Ratio) of mortality among older adults with impairment in each component of the phenotype, considering p